Design of the nozzle of a yarn suction gun for fully drawn yarn. Issue 3 (February 2014) - Li, Yonggui; Wei, Man; Zhang, Lingfang; Chen, Dongsheng
The yarn suction gun is a kind of fluid machinery using compressed air as power. Airflow geometry in the gun has a significant influence on the airflow distribution, which decides the yarn suction performance. To clarify the effect of the nozzle structure on the yarn suction performance, we designed 16 nozzles, determined yarn suction force F, mass flow rate of compressed air G and analyzed yarn suction efficiency η, which is defined as the ratio of F to G . The rational geometrical parameters are obtained as follows: the number of jet orifices N  = 3, jet orifice diameter d  = 1.6 mm, jet orifice angle Φ  = 75° and passage diverging angle of the nozzle θ  = 60°. A smaller N reduces the conflict between jet streams and then increases η . Decreasing d contributes to greater η but smaller F . In the range of Φ  ≤ 75, increasing Φ causes both F and η to increase. An appropriate θ promotes the yarn suction performance by helping the injected air to go forward smoothly and reducing backflow. It is more rational to use η to evaluate the yarn suction performance.